The well-being of people in Kota Bharu Kelantan / Wan Najihah W.Rasidi - W.Rasidi, Wan Najihah (2013)
This research is conducted to examine the well-being of residents in Kota Bharu. This study seeks to know how people evaluate their well-being, proxied by happiness. The objective of this research is to determine whether the independent variables which are personal financial affair, social & family relationship, health, employment and environment influence the dependent variable which is well-being of people proxied by happiness or not. In this research, a questionnaire was distributed among the people in Kota Bharu, Kelantan. A sample of 100 people had been chosen. The results show that there are significant relationships between personal financial affair and social and family relationship with people’s well-being while health, employment and environment are not significant with the people’s well-being.